2017
DOI: 10.1186/s13046-017-0575-4
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin is overexpressed and regulated by mutant p53 in oral squamous cell carcinoma

Abstract: BackgroundThe aim of this study was to investigate the oncogenic function and regulatory mechanism of stathmin in oral squamous cell carcinoma (OSCC).MethodsTwo-dimensional electrophoresis and liquid chromatography-tandem mass chromatography were applied to screen differentiated proteins during carcinogenesis in OSCC. Cell Counting Kit-8 (CCK-8) assays, colony formation, migration, flow cytometry, immunofluorescence and a xenograft model were used to detect the function of stathmin. The correlation between sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
1
33
0
2
Order By: Relevance
“…Immunohistochemistry (IHC) and immunofluorescence were performed as described in our previous study [18], with primary antibodies against PD-L1, galectin-9, H3K27ac and GCN5 (Cell Signaling Technology, Danvers, MA, USA), and Ki-67 (Proteintech, Rocky Hill, NJ, USA). The staining intensity was assessed as follows: 0 = negative; 1 = weak; 2 = moderate; 3 = strong.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry (IHC) and immunofluorescence were performed as described in our previous study [18], with primary antibodies against PD-L1, galectin-9, H3K27ac and GCN5 (Cell Signaling Technology, Danvers, MA, USA), and Ki-67 (Proteintech, Rocky Hill, NJ, USA). The staining intensity was assessed as follows: 0 = negative; 1 = weak; 2 = moderate; 3 = strong.…”
Section: Methodsmentioning
confidence: 99%
“…The primary antibodies included stathmin (#ab52630, 1:500 dilution; Abcam), Ki‐67 (#19972‐1‐AP, 1:50 dilution; Proteintech) and Bub1 (budding uninhibited by benzimidazoles 1, #13330‐1‐AP, 1:100 dilution; Proteintech). Stathmin immunohistochemical staining score was evaluated as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Stathmin, an important microtubule‐destabilizing protein, is shown to be overexpressed in many human malignancies, including hepatocellular carcinoma and lung, gastric, breast, and head and neck cancers . Our previous study suggested that stathmin acts as an oncogene and could be a potential antitumor therapeutic biomarker in OSCC . Several studies have shown that overexpression of stathmin influences the resistance of docetaxel and cisplatin .…”
Section: Introductionmentioning
confidence: 99%
“…101 Corroborating these observations, STMN1 inhibition in cancer cells harboring TP53 mutation has decreased cell proliferation and viability, increased apoptosis and suppressed tumorigenicity, suggesting that STMN1 is required for the survival of p53--mutant cells. [102][103][104][105] Recently, it was suggested that overexpressed STMN1 interacts with p53 and contributes to the gain-of-function of p53. 105 Altogether, these data suggest that targeting STMN1 may be an interesting approach to treat different types of cancers with aberrant p53 function.…”
mentioning
confidence: 99%
“…[102][103][104][105] Recently, it was suggested that overexpressed STMN1 interacts with p53 and contributes to the gain-of-function of p53. 105 Altogether, these data suggest that targeting STMN1 may be an interesting approach to treat different types of cancers with aberrant p53 function.…”
mentioning
confidence: 99%